Upper-arm hemodialysis access in Sweden. Issue 1 (March 2017) - Hedin, Ulf; Welander, Gunilla
Aim: To provide the contemporary use of upper-arm access for hemodialysis in Sweden using data from a unique national registry for hemodialysis access. Methods: Data were retrieved from a nation-wide registry for dialysis access in Sweden, Dialysis Access Database (DiAD) on the use and function of specific access types with a focus on upper-arm accesses. Results: The data demonstrate an increased use of upper-arm access, likely dependent on a changing patient population, with brachiocephalic arteriovenous fistula (AVF) as the most common access type. Women received more upper-arm accesses than men. Given the recent establishment of the registry, patency and access function can at this point give preliminary data. Indications of a better function for brachiobasilic AVFs in staged procedures were observed as well as for upper-arm arteriovenous grafts (AVGs) in women. Conclusions: Registry data support an increased use of upper-arm accesses, especially in women. The study also demonstrates the potential of a dedicated national access registry to improve access care.